A versatile plasmid system for reconstitution and analysis of mammalian ubiquitination cascades in yeast - Avagliano Trezza, Rossella (Microb Cell, 2017)
Ubiquitination is a posttranslational protein modification that regulates most aspects of cellular life. The sheer number of ubiquitination enzymes that are present in a mammalian cell, over 700 in total, has thus far hampered the analysis of distinct protein ubiquitination cascades in a cellular context. To overcome this complexity we have developed a versatile vector system that allows the reconstitution of specific ubiquitination cascades in the model eukaryote Saccharomyces cerevisae (baker’s yeast). The vector system consists of 32 modular yeast shuttle plasmids allowing inducible or constitutive expression of up to four proteins of interest in a single cell. To demonstrate the validity of the system, we show that co-expression in yeast of the mammalian HECT type E3 ubiquitin ligase E6AP (E6-Associated Protein) and a model substrate faithfully recapitulates E6AP-dependent substrate ubiquitination and degradation. In addition, we show that the endogenous sumoylation pathway of S. cerevisiae can specifically sumoylate mouse PML (Promyelocytic leukemia protein). In conclusion, the yeast vector system described in this paper provides a versatile tool to study complex post-translational modifications in a cellular setting.